Sexual Development of Adolescents in the Tomsk Region - Ivan А. Deev; Ivan L. Kolomeets; Tatiana V. Saprina; Olga S. Kobyakova; Elena М. Kamaltynova; Evgeny S. Kulikov; Alena N. Levko; Kristina V. Kulikova; Viktoriya I. Yurkova (Union of pediatricians of Russia, 2017)
Background. Sexual development of adolescents is one of the important indicators of the population well-being, the study of which, in the context of the world trend towards a change in the period of puberty, can contribute to the identification of public health problems. Objective. Our aim was to study the basic indicators of sexual development of adolescents and to determine the regional characteristics of this population. Methods. The evaluation of secondary sexual characteristics was carried out by specialists according to Tanner criteria. Ultrasound examination of organs of the reproductive system was carried out using a portable scanner Mindray M7. The analysis of the results was carried out taking into account the gender, living conditions, physical development. Results. We examined 7,120 adolescents aged from 13 to 16 years. The degree of axillary hair distribution by Tanner criteria was 2.4±0.7 in young men, 2.9±0.4 - in girls, pubic hair - 2.0±0.9 and 2.6±0.8, respectively. The indicator of development of mammary glands by Tanner criteria in girls was 2.6±0.8, menstrual function by Tanner criteria - 2.4±0.8. Herewith, urban adolescents had later terms of appearance of the secondary sexual characteristics in comparison with the inhabitants of rural areas. Conclusion. We registered the delayed sexual development in 8.1% of girls and 13.6% of young men. Urban youths have experienced a delay in gonadal growth. Among the female population there was an outstripping growth and development of the uterus and ovaries in comparison with rural adolescents.